MARINE DEBRIS IN THE SPECIAL REGION OF YOGYAKARTA: ISSUES, IMPACTS, AND PROPOSED SOLUTIONS (Prosiding dan Call Paper Widya Wiwaha, 2025)
Marine debris has become a critical environmental challenge in the Special Region of Yogyakarta (DIY), driven by land-based waste leakage, rapid tourism growth, and inadequate waste management infrastructure. This study identifies the dominant types, sources, and impacts of coastal waste in DIY and offers policy recommendations for sustainable coastal management. Using a qualitative descriptive approach based on literature review and secondary environmental data, the study finds that plastic-based macro and meso debris dominate coastal waste composition, posing significant ecological threats, including habitat degradation and marine species mortality. The accumulation of waste also causes socioeconomic losses through decreased fishery productivity, reduced tourism attractiveness, and increased coastal clean-up costs. This research underscores the need for integrated waste governance, community participation, behavioral change interventions, circular economy approaches, and strengthened institutional coordination. These measures are essential to ensure the long-term sustainability of Yogyakarta’s coastal ecosystems.
Keywords: Marine Debris; Coastal Pollution; Plastic Waste; Yogyakarta; Sustainable Coastal Management; Circular Economy.